A crítica jornalística de cinema na internet : um dispositivo em transformação - Carolina Braga (2013)
This thesis aims to investigate how the characteristics of media ecosystem of Internet influence journalistic film criticism in the network. In this way, we used some key concepts to discuss the transformation of the format, like: the perspective of the device, the theory of journalistic genres, the historical course of journalistic criticism and the characteristics of contemporary media ecosystem. Starting with these references, we implemented a design methodology that enabled us to verify, in practice, the interference generated on the format. Thus, we recognize the critical journalistic film on the internet as a communication process with language features and socialparticipation own by the network. We believe that there is a process of critical traffic communicative logics. Such processing involves, for example, the incorporation of hypertext language, audiovisual resources and the endless possibilities opened up by participation. The choice by recognizing and treating criticism as a device in transformation approach responds to that criticism journalistic film on the internet have other dimensions as well as having the operating mode changed.